Peningkatan Dalam Menyusun Rencana Pelaksanaan Melalui Supervisi Klinis Pada Kepala SD Daerah Binaan II UPTD Pendidikan Kecamatan Kalikotes Kabupaten Klaten Semester Gasal Tahun Pelajaran 2014/2015 - Sumarsih, Sri (Jurnal Varidika: Varia Pendidikan, 2014)
The aim of this study was to describe the increase in the principalâs efforts in preparing the implementation plan through clinical supervision at State Primary School Pa tronage II Regional District of Klaten Kalikotes odd semester of 2014/2015 academic year. Subject and source of research data were five school principals. Methods of data collection were observation, documentation, and testing. Data analysis used a critical and compara- tive analysis. Indicators of success used the minimum 76 and a target of 100% complete- ness. Results of research and discussion suggest that the observation of the principal in the supervision of lesson preparation plan in detail can be described from previsus cycle Â to cycle I, there was an increase of 60%, from cycle to cycle II, there is an increase of 80%, and from the first cycle to the second cycle previsus there is an increase of 20%, it can be concluded that the start of the second cycle to previsus cycle is significantly, and principals in the preparation of the lesson plan in detail can be described from previsus cycle to the first cycle, an increase of 60%, from previsus cycle to second cycle, an increase of 100%, and from the first cycle to the second cycle there is an increase of 40%, it can be concluded that the start of the second cycle to before cycle is significantly.